Even the dead [compact disc, unabridged] : a Quirke novel - Black, Benjamin, 1945- (Macmillan Audio, 2015)
Perhaps Quirke has been down among the dead too long. Lately the Irish pathologist has suffered hallucinations and blackouts, and he fears the cause is a brain tumor. A specialist diagnoses an old head injury caused by a savage beating? all that's needed, the doctor declares, is an extended rest. But Quirke, ever intent on finding his place among the living, is not about to retire.